2022
DOI: 10.1155/2022/7080579
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning and Digital Information Technology in Volleyball

Abstract: Since the 1980s, machine learning has attracted extensive attention in the field of artificial intelligence. Following the expert system, it opened a precedent for the application of machine learning in the field of artificial intelligence and became one of the important topics of artificial intelligence. However, in the field of volleyball, the application of machine learning and information technology in volleyball is extremely limited. Volleyball has not developed widely in society nor has it become a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…If we have to define machine learning, we can say that it is computer programs that can improve their processing power by themselves based on experience. When the effect of athletic level of volleyball players on decision making, accuracy, reaction time and cognitive level in hitting, landing, and blocking was analyzed by machine learning method, it was concluded that the higher the athletic level, the less the players were affected by other factors (Yu et al, 2022). However, factors such as motion blur due to ball speed, low camera frequency or noisy ball contour (excessive exposure time causes blurring and stretching of the ball contour), lighting or changing environmental conditions (player and spectator movements in the background) can reduce accuracy.…”
Section: Video Analysis Systemmentioning
confidence: 99%
“…If we have to define machine learning, we can say that it is computer programs that can improve their processing power by themselves based on experience. When the effect of athletic level of volleyball players on decision making, accuracy, reaction time and cognitive level in hitting, landing, and blocking was analyzed by machine learning method, it was concluded that the higher the athletic level, the less the players were affected by other factors (Yu et al, 2022). However, factors such as motion blur due to ball speed, low camera frequency or noisy ball contour (excessive exposure time causes blurring and stretching of the ball contour), lighting or changing environmental conditions (player and spectator movements in the background) can reduce accuracy.…”
Section: Video Analysis Systemmentioning
confidence: 99%
“…The system can learn from past data and patterns, accurately identifying new patterns and movements [18]. The system can also optimize its decision-making processes, considering system performance, resource utilization, and security requirements [19]. In Volleyball, DSS integrated with edge computing, ISCC, optimization, and machine learning can analyze player and team movements, identify strengths and weaknesses, and generate insights for decision-makers [20].…”
Section: Introductionmentioning
confidence: 99%